Strategies to Maximize Physical Education by Online or Offline Post Pandemic (Universitas Negeri Semarang, 2022)
Abstract: After the COVID-19 pandemic, Online Sports and Health Physical Education (PE) has become essential for the sustainability of students' fitness and physical activity. However, many PE teachers are not ready to adapt to learning in the current new average era. The learning situation has not fully